Occupational risks in cattle slaughter: Classification by severity degree (Research, Society and Development, 2021)
Introduction: The way of working and the tools used during the production process of the slaughterhouse industry promotes the occurrence of occupational accidents and the rise of respiratory and musculoskeletal diseases. Objective: The objective is to identify and classify the existing risks regarding its severity degree, in a plant located in the city of Governador Valadares / MG. Methods: The risk analysis considered only activities related to the slaughter of cattle, including stunning, bleeding, skinning, evisceration and carcass cutting. The research is qualitative and exploratory, and all the information regarding working conditions were obtained from another research done by the same author at the same plant. Therefore, for technical procedures, the research is characterized as a bibliographic review and a case study. Results: The Preliminary Risk Analysis - PRA enabled the identification and classification of the following risks: ergonomic, accident, biological, falling from the same level, humidity, electric shock, noise and vibration. Intervention measures were suggested to mitigate the risks identified during the study, according to the current labor law. Conclusion: Through the risk’s classification it is possible to prioritize the preventive measures at the activities where more severe risks were identified, such as the use of chainsaw and a possible attack of the animal.